Planering av vägupprustning med hjälp av GIS och optimering : en fallstudie på Holmen Skog - Westberg, Johan (SLU/Dept. of Forest Resource Management, 2007)
The objective of this thesis was to develop a method for the planning of road upgrading at Holmen Skog, a Swedish forest company. A critical issue for creating such plans is to identify roads that are suitable to upgrade to a standard that can handle heavy traffic during spring thaw, since spring thaw is a bottle neck for transporting timber. The method was tested in a case study at a district.